E-Service Quality and e-Loyalty: Examining the Mediating Roles of e-Trust and e-Satisfaction Female Online Shoppers - Nadia Ika Purnama; Siti Mujiatun (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2025)
Purpose—This study examines the impact of e-service quality on e-loyalty among female online shoppers in Medan, with e-trust and e-satisfaction as mediating factors.Methodology—The research population of research population is all female people in Medan City who are making online purchases on Facebook and Instagram applications. This study used a non-probability sampling method, using an online questionnaire administered through Google Forms to collect data from 170 people. Data were analyzed with the help of the SmartPLS program and structural equation modeling. Findings – The results showed that e-service quality positively and significantly affects e-satisfaction (p0.05). E-service quality positively and significantly affects e-trust. E-service quality positively and significantly affects e-loyalty. E-satisfaction positively and significantly affects e-loyalty. E-trust positively and significantly affects e-loyalty. E-satisfaction positively and significantly plays a role in mediating the effect of e-service quality on e-loyalty. E-trust positively and significantly plays a role in mediating the effect of e-service quality on e-loyalty.Originality/Novelty – This research model includes four variables and utilizes the notion of mediation by using SEM-PLS to evaluate each relationship in the model.Implications—This study's results are expected to be input and a foundation for Facebook and Instagram application users and companies, helping them determine the right strategy to increase consumer e-loyalty.